2002
DOI: 10.1002/j.2050-0416.2002.tb00535.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fatty Acid and Sterol Analyses as Quality Control Methods in the Brewing Industry

Abstract: Fatty acid and sterol analyses were evaluated as alternative quality control methods to conventional differentiation and characterisation systems in the brewing industry. The presence of linoleic acid (18:2) in brewing yeast could be used to distinguish these from closely related yeast species. Furthermore, the absence of lanosterol and stigmasterol enabled differentiation of the brewing yeast from the rest of the closely related species tested. However, both fatty acid and sterol methods were not sensitive en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…All of these techniques are time-consuming and expensive and electronic noses and tongues are not selective. 2,3,5,11,13,14,23 The brewing of beer is a typical example of a food production process. Despite economic interests such as cost reduction and short duration of the production process, the product quality should be assured for the consumer with regard to taste.…”
Section: Introductionmentioning
confidence: 99%
“…All of these techniques are time-consuming and expensive and electronic noses and tongues are not selective. 2,3,5,11,13,14,23 The brewing of beer is a typical example of a food production process. Despite economic interests such as cost reduction and short duration of the production process, the product quality should be assured for the consumer with regard to taste.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, samples have to be taken and analyzed in a laboratory, thus requiring time consuming steps like sample pre-treatment, pre-concentration and finally e.g. gaschromatographic and mass spectroscopic analyses [1][2][3][4][5][6][7][8]. Small and medium size enterprises cannot maintain an own laboratory due to the high cost and therefore have to take care of the process development by higher safety standards, safety extensions of the processes or external analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cellular fatty acid analysis has proved to be successful in distinguishing between Saccharomyces yeasts and other genera 3 . Earlier studies have shown difficulty in differentiating between sub species of yeasts 25 , although a more recent study by Morakile and co-workers 24 proved cellular fatty acid and sterol analysis to be a useful tool for differentiating between brewing strains and related yeasts. However, the methods failed to distinguish brewing strains from a derived variant.…”
Section: Introductionmentioning
confidence: 99%